A Study of the Effectiveness of Learning Management Computing Science Using the Tatuca Classroom Online Classroom Combined with the Flipped Classroom Learning Management Method for 4th Grade Students - Kudaphan, Phanit; Pongpisanu, Sudaporn; Boonkusol, Thongpan (Saengtham College Journal, 2026)
This research has the following objectives: 1. To study academic achievement of students in grade 4 through learning management Computing Science using the Tatuca Classroom online classroom together with the Flipped Classroom learning management. 2. To study student satisfaction with learning management Computing Science using the Tatuca Classroom online classroom together with the Flipped Classroom learning management. Statistics used in data analysis included frequency distribution, average, percentage, and hypothesis testing. The results of the research found that all 34 sample students had an improvement in academic achievement in subjects. Computational science: Internet usage and data presentation with software for 4th Grade students after passing learning management Computing Science using the Tatuca Classroom online classroom together with the Flipped Classroom learning management. After studying, it was significantly higher than before studying at the .05 level, and students’ satisfaction with learning the subject. Computational science: Internet usage and data presentation with software for 4th Grade students was at the highest level, with an average of 4.57.